2022
DOI: 10.1007/jhep01(2022)070
|View full text |Cite
|
Sign up to set email alerts
|

Finite size spectrum of the staggered six-vertex model with Uq($$ \mathfrak{sl} $$(2))-invariant boundary conditions

Abstract: The finite size spectrum of the critical ℤ2-staggered spin-1/2 XXZ model with quantum group invariant boundary conditions is studied. For a particular (self-dual) choice of the staggering the spectrum of conformal weights of this model has been recently been shown to have a continuous component, similar as in the model with periodic boundary conditions whose continuum limit has been found to be described in terms of the non-compact SU(2, ℝ)/U(1) Euclidean black hole conformal field theory (CFT). Here we show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…From our discussion above we know that only the alternating or quasi periodic staggering leads to a local Hamiltonian. Both cases have been studied extensively in [27,28] and [26] respectively. Using the vertex representation of the Temperley-Lieb generators e i,i+1 :…”
Section: ) Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…From our discussion above we know that only the alternating or quasi periodic staggering leads to a local Hamiltonian. Both cases have been studied extensively in [27,28] and [26] respectively. Using the vertex representation of the Temperley-Lieb generators e i,i+1 :…”
Section: ) Modelmentioning
confidence: 99%
“…Remarkably, the choice of boundary conditions has a profound influence on the low energy properties of the staggered models: the effective theory of (5.9) with anisotropy γ < 2δ 0 < π − γ has been identified to be the SL(2, R)/U(1) sigma model at level k = π/γ with a noncompact spectrum of conformal weights [27,28]. On the contrary, Robertson et al found that the continuum limit of the model (5.10) is compact [47].…”
Section: Spectral Flow Between the Integrable Pointsmentioning
confidence: 99%
See 3 more Smart Citations